SPECIFICS OF PROJECT MANAGEMENT IN SELECTED ORGANIZATIONS PROVIDING SOCIAL SERVICES - Denisa Dufková; Radka Prokešová; Jitka Vacková; Lesia Shuranova (Клінічна та профілактична медицина, 2025)
Introduction. Project management is a key element that contributes to social service organizations' effective functioning and development. According to the literature, social projects can be funded from various sources, including government grants, private donations, and organizations' revenues. However, to ensure the successful implementation of projects, systematic management and careful planning are required, which is achieved through project management techniques.